Safety Nets and Turning Points: Managing Collaboration and Innovation for Teacher Efficacy in Teaching Assistant Program - Alfin Mustikawan; Ahmad Rosikhul Fahmi; Moh. Aditya Hadi Saputra; Ahmad Albert Afrilsyah (Universitas Sarjanawiyata Tamansiswa, 2026)
This study explores the managerial dynamics of the Teaching Assistant Program (TAP) in bridging the theory-practice gap for pre-service teachers. It investigates how collaboration and innovation are managed to form professional self-efficacy within an Islamic higher education context. Employing a transcendental phenomenological design, this study analyzed the lived experiences of eight pre-service teachers selected through purposive sampling. Data were gathered via in-depth interviews to 8 informants and analyzed using systematic thematic analysis. The study reveals that teacher efficacy is not a static outcome but a dynamic construction forged through the interplay of